Nullology (O'Reilly Media, 2014)
"Nullology is the study of the empty set. Sets per se crop up all over the place in the relational world; the question is -- and it's a crucial one -- what happens if the set under consideration happens to be empty? For example, a relation contains a set of tuples: what about the possibility of a relation containing no tuples at all? Now, this particular possibiloty is reasonably familiar, because a relation with no tuples behaves much like a file with no records. But even in this case, there are some interestng aspects to consider that are probably unfamiliar to most database professionals. And there are many other places in the relational world where the empty set rears its head, several of them both unfamiliar and of fundamental importance."--Resource description page.